AETIOLOGY OF SUDDEN CARDIAC DEATH IN FORENSIC MEDICAL PRACTICE AND AND SELECTION OF CASES FOR POST-MORTEM GENETIC TESTING – 5 YEAR RETROSPECTIVE STUDY - Srpanova, Viktorija Belakaposka; Bitoljanu, Natasha; Ivcheva, Ana; Cakar, Ljupcho; Pavlovski, Goran; Stankov, Aleksandar; Jakovski, Zlatko (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Sudden cardiac death (SCD) is a term used to describe death in a person who has no previously diagnosed heart disease, or is not expected to die at that stage of the disease. SCD is considered a major health problem in the world, accounting for 15-20% of all deaths, and the mechanism of its occurrence includes the development of ventricular tachycardia, which progresses to ventricular fibrillation and finally asystole. SCD is generally seen in the older population; however, a significant mortality rate is also observed in young people with hereditary heart pathology. The use of substances that can have an effect on cardiac function is associated with many cases of SCD, so toxicological substances should always be considered by forensic doctors and screening tests should always be performed. The aim of this research is to analyze the causes of sudden cardiac death and to select cases in which post-mortem genetic testing is indicated.   For this purpose, a review was made of the autopsies performed at the Institute of Forensic Medicine between 2018 and 2022, the biochemical and toxicological findings of the various causes of death were analyzed, and the cases where the exact cause of sudden cardiac death was not determined were also analyzed. In the analyzed period of 5 years, the cases with cardiomyopathy dominated, followed by coronary artery heart disease, and in 20 percent of the cases the exact cause of death was not determined. Men dominated with a percentage representation of 80%. Keywords: Sudden cardiac death, Troponin I, toxicology, post-mortem genetic analysis. https://doi.org/10.55302/JMS2361075bs